Changes of Germination and Seedling Growth of Soybean after Seed Coating with Microbial Inoculant Bacillus thuringiensis and Beauveria bassiana - Kangsopa, Jakkrapong; Sompoch, Potsathorn; Yodsri, Somjai; Jeephet, Phetcarat (YRU Journal of Science and Technology, 2021)
Chiang Mai 60 (CM 60) and Sor Jor 5 (SJ 5) are two popular types of soybeans grown among farmers since they have long been extension seeds. The seeds are prone to being destroyed by diseases and insects during the cultivation phase, harvesting phase, and seed storage phase. This experiment aims to study the results of coating seeds with Bacillus thuringiensis formula 4 (MMO4) and Beauveria bassiana formula 5 (MMO5) in different ratios to observe the changes in germination and growth of SJ 5 soybean seedlings. The experiment was divided into eight groups which are uncoated seeds T1), seeds coated with Carboxymethyl cellulose T2), seeds coated with 0.1-0.3 ml. of MMO4, respectively T3-T5), seeds coated with 0.1-0.3 ml. of MMO5, respectively T6-T8). The experiment results are as follows. Seeds coated with Carboxymethyl cellulose and seeds coated with 0.1 ml. and 0.2 ml. of MMO5 had better radical emergence compared to uncoated seeds. Additionally, seeds coated with all methods had better germination compared to uncoated seeds. When tested under greenhouse conditions, seeds coated with all ratios of MMO5 had grown into seedlings with a longer shoot length and total seedling length compared to uncoated seeds tested under laboratory condition. At the same time, seeds coated with all ratios of MMO5 had grown into seedlings with a longer shoot length compared to uncoated seeds when tested under greenhouse condition. As a result, 0.1 ml. of MMO5 is a recommended ratio to coat soybean seeds since it is the most cost-effective and has the best effect on the soybean seed quality.